Experimental study on the effects of fin pitches and tube diameters on the heat transfer and fluid flow characteristics of a fin punched with curved delta-winglet vortex generators. (5th June 2017) - Wu, Xiang; Lin, Zhi-Min; Liu, Song; Su, Mei; Wang, Liang-Chen; Wang, Liang-Bi
Highlights: Effects of fin pitches and tube diameters on the air side Nusselt number and friction factor are evaluated. CDVGs can effectively enhance heat transfer compared with the counterpart plain fin geometry. The best performance can be achieved with the combination of the largest fin pitch and the smallest tube diameter. Optimum fin pitch and tube diameter are less influenced by Reynolds number. Abstract: The effects of fin pitches and tube diameters on the air side heat transfer performance of a tube bank fin heat exchanger using curved delta-winglet vortex generators (CDVGs) were experimentally investigated, and the counterpart plain fin was selected as a reference for optimizations of fin geometries. Totally 18 samples with three different fin pitches and three different tube diameters were studied for the fin with/without CDVGs. Based on the experimental data and their corresponding fitting formula, the effects of the fin pitches and tube diameters on heat transfer performance of the fin with or without CDVGs were discussed, and the correlations of air side Nusselt number and friction factor with Reynolds numbers, fin pitches and tube diameters were obtained. The results indicate that the fin patterns with CDVGs could effectively enhance heat transfer performance compared with the counterpart plain fin under identical pump power constraint, and their heat transfer enhancement performances are dependent on the flow condition and the fin's geometry parameters. In the range of studied geometry parameters and Reynolds numbers, the best performance could be achieved with the combination of the largest fin pitch and the smallest tube diameter, and the optimum parameters are less influenced by the Reynolds number.